Analisis Pengaruh Lingkungan Kerja Dan Job Embeddedness Terhadap Kepuasan Kerja Karyawan Pada PT Ramotindo Pakuon Persada - Namira Salsabila; Etika Sabariah (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
PT Ramotindo Pakuon Persada is a micro, small and medium enterprise engaged in the field of panel makers and electrical shops. Businesses in this company have a fairly high job risk related to electricity and have a fairly high work pressure. The purpose of this study was to determine how much influence the work environment and job embeddedness have on employee job satisfaction at PT Ramotindo Pakuon Persada. This study uses a quantitative method with saturated sampling. The sample in this study were 34 respondents. The work environment has a t count > t table (2.327 > 2.039) with a significant value of 0.027 <0.05, which means that the work environment influences job satisfaction. Job embeddedness has a t count > t table (2.225 > 2.039) with a significant value of 0.03 <0.05, which means that job embeddedness has an effect on job satisfaction. The work environment and job embeddedness have a significant value of 0.000 <0.05, which means that the work environment and job embeddedness have a significant simultaneous effect on job satisfaction. The results of this study can be used as input for related companies and can be used as an evaluation to increase job satisfaction by taking into account several factors such as noise that arises, a supportive work environment and increasing family relationships among employees.